2014
DOI: 10.4064/sm224-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of associate spaces of weighted Lorentz spaces with applications

Abstract: We characterize the associate spaces of weighted Lorentz spaces GΓ(p, m, w) and present some applications of this result including necessary and sufficient conditions for a Sobolev-type embedding into L ∞ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Remark 3.3(i)) points x k , y k ∈ (0, t k ) such that Define t k−1 := min{x k , y k }. Then (6) and (7) are both satisfied and one of the identities (8) and (9) holds true as well. One continues by induction, replacing k with k − 1 and repeating Step 2.…”
Section: Discretization Of the Copson-lorentz Functionalmentioning
confidence: 86%
See 1 more Smart Citation
“…Remark 3.3(i)) points x k , y k ∈ (0, t k ) such that Define t k−1 := min{x k , y k }. Then (6) and (7) are both satisfied and one of the identities (8) and (9) holds true as well. One continues by induction, replacing k with k − 1 and repeating Step 2.…”
Section: Discretization Of the Copson-lorentz Functionalmentioning
confidence: 86%
“…One of the few examples of rearrangement-invariant spaces whose embedding into Λ was successfully and satisfactorily characterized are the Γ spaces, including their generalized variants. The results of this type were obtained in [6,7] by a method of discretization. Various steps in this direction were made even earlier, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using the assumption of integrability at the origin of u, one may show then by integration by parts that the above expression is equivalent to A (16) . While handling the second term in the sum, one also needs to use Proposition 2.1.…”
Section: Consider Now the Case (I) It Holdsmentioning
confidence: 99%
“…The "K-spaces" were defined in [18], where they appeared as optimal spaces in certain Youngtype convolution inequalities. Besides that, in [16] it was shown that the associate space to the generalized Γ space is also a "K-space". Now, let us briefly present some background to the problems we are about to investigate.…”
mentioning
confidence: 99%
“…Then by[1] Theorem 7, we have GΓ(p, r; w) = (L (p,β , L (p,α ) θ,r .Thus, using duality relation of real interpolation spaces (see, for instance,[5] Theorem 3.7.1), we get[GΓ(p, r; w)] ′ = (L p ′ ),β , L p ′ ),α ) θ,r ′ = (L p ′ ),α , L p ′ ),β ) 1−θ,r ′ ,finally, an application of Theorem 3.6 completes the proof. In view of Lemma 2.4 , we get the following equivalent norm on [GΓ(p, r; w)] ′ :f [GΓ(p,r;w)] ′ ≈   Log t) − r ′ δ rwhich is apparently simpler than the one which follows from[14] Theorem 1.1 (vi).…”
mentioning
confidence: 99%